Analysis of interfacial structure and bond strength of self-etch adhesive systems - Pinzon, Lilliam M (2013)
PURPOSE: To determine the bond strength, nanoleakage and interfacial morphology of four self-etch adhesives bonded to superficial dentin. METHODS: Micro-tensile (MT, n=15) and single plane shear (SP, n=8) bond tests were performed using human dentin polished through 320-grit SiC paper. Clearfil Protect Bond (PB), Clearfil S(3) Bond (S3), Prompt L-Pop (PLP) and G-BOND (GB) were used according to manufacturers’ instructions. Composite was applied as cylinders with a thickness of 4 mm with a 1-mm diameter and stored in water at 37° C for 24 hours. Specimens were debonded with a testing machine at a cross-head speed of 1 mm/min. Means and standard deviations of bond strength were calculated. Data were analyzed using ANOVA. Fisher’s PLSD intervals were calculated at the 0.05 level of significance. Failure modes were determined at 100X. The hybrid layer was revealed by treatment with 5N HCl/5% NaOCl or fractured perpendicular to the interface and sputter coated with gold. Specimens were viewed at 1000X, 2500X, and 5000X in a field emission SEM at 15 kV. Teeth (n=2) sectioned into 0.9-mm thick slabs were immersed in ammoniacal silver nitrate solution for 24 hours, rinsed and immersed in photo-developing solution for 8h. Specimens were sectioned (90-nm thick) and observed under TEM. RESULTS: Means ranged from 25.0 to 73.1 MPa for MT and from 15.5 to 56.4 MPa for SP. MT values were greater than SP, but were highly correlated (R(2) = 0.99, p= 0.003) and provided the same order for the systems studied. Fisher’s PLSD intervals (p<0.05) for bond strength techniques and adhesives results were 1.7 and 2.3 MPa, respectively. Failures sites were mixed. TEM showed that hybrid layers were ~0.5 µm for PB, GB and S3 and ~5 µm for PLP. SEM showed morphologic differences among adhesives. Silver nitrate deposits were observed within interfaces for all adhesive systems. CLINICAL SIGNIFICANCE: Simplification of application procedures appears to induce loss of adhesion capabilities. In this in vitro study we evaluated the bond strength, the micro and nano morphology of four self-etch adhesive systems. In summary, the microtensile bond strengths ranged from 25 to 73 MPa. None of the adhesive systems tested was able to totally prevent nanoleakage, but there were differences among systems. No relationship was observed between thickness of the hybrid layer and bond strength.